A construção da personagem pelo duplo viés biográfico e autobiográfico no dueto conto e romance de Graciliano Ramos: Infância e A terra dos meninos pelados - Silva, Ana Paula da (2009)
The memoirist registry, in general, can involve multiple dimensions and functions in its peculiar speech. The main purpose of this dissertation is to investigate the various shortcuts in writing, by which the Graciliano Ramos´s autobiographical project shows us some kind of memoirist biases in their literary and fictional novel with cognitive, social and psychological aspects. In particular, the writer, through the technical report of his experience when he was a child (The Land of the Naked Boys, 1939) wished to redeem his personal identity, social or national, to defend the memory of the adult who keeps within himself the sense of a life in embryo, as the object of reflection (Childhood, 1945). We selected, from these assumptions, two genders and two works: the memoirist novel Childhood and short story The land of the Naked Boys to demonstrate, at the confluence short story and novel, the chronological unfolding of his awareness as the character Raimundo, seeking the disclosure of the biography or the autobiography of the Brazilian writer Graciliano Ramos. The first chapter deals with the concepts applied to the two works in the ambiguity of the generic form: Autobiography or memories? Story or novel? It aims to clarify the difference between memory and remembrance in both works and realize the structure of that innovative writing. The second chapter explores the concept of exotopy according to Bakhtin. At the same time, it speculates the inclusion of both adult and child views of the narrator mixed in a dialectical relation with the external social assistance, a concept of extraction of historical substrate. The third chapter explains the concept of bio grapheme and bio diagram, according to Roland Barthes, the corpus extracted from the excerpts attached to the dissertation, in order to configure the profile of the writer in his critical-poetic universe that permeates the novel Childhood work in an operational work of approaching to the short story The land of the Naked Boys while revealing the literary-aesthetic project since its genesis or history. In the conclusion, we focused the concept of novel and the first autobiographical marks of the arising genre, from the procedure of comparing two works, in which contrasting, according to our view, it is able the observation of the profile and the aesthetic consciousness of the writer Graciliano Ramos, inaugurating the memoirist autobiographical novel in the first half of the twentieth century, in the Brazilian Literature